Leukocyte and endothelial cell interactions in sepsis: relevance of the protein C pathway - Joyce, David E; Nelson, David R; Grinnell, Brian W (Critical care medicine, 2004)
To give an overview of leukocyte and endothelial cell interactions in sepsis and to explore the role of the protein C pathway in modulating the innate immune response via its anti-inflammatory properties. Novel in vitro data and a MEDLINE search for the terms "activated protein C," "recombinant human activated protein C," "inflammation," "leukocyte adhesion," and "sepsis" were used, along with clinical trial databases from the PROWESS trial and a phase I human endotoxin trial evaluating recombinant human activated protein C (drotrecogin alfa [activated]). The protein C pathway is positioned at the interface between the endothelium and the leukocyte response of the innate immune system. Activated protein C (APC) possesses profibrinolytic, anti-inflammatory, and anti-apoptotic properties, acting as an endothelial cell and microvascular modulator in opposition to thrombin and the proinflammatory cytokines. Distribution of the receptor for APC, endothelial protein C receptor, was detected on effector cells of the innate immune response. This suggests a further role for the protein C pathway in regulating inflammation. In neutrophils and eosinophils, an endothelial protein C receptor-mediated APC response leads to reduced migration in response to cytokine gradients. Endothelial protein C receptor may also suppress the apoptotic response in monocytes and enhance the expression of the adhesion integrin CD11b in granulocytes. The microvascular, anti-inflammatory influence of APC in sepsis is supported by suppression of endothelial cell adhesion molecules and the ability of APC to protect the endothelium from inflammatory insult. The coordinated effects of the protein C pathway on the endothelium and the leukocyte response of the innate immune system are supported by potential restriction of endothelial protein C receptor expression to cells of the innate immune system and by suppression of adhesion molecule expression on the endothelium by APC. Reduced neutrophil migration in response to cytokines is also mediated by endothelial protein C receptor. Further clinical studies will be needed to define the intrinsic role of the protein C pathway in coordinating the innate immune response in endothelium-based inflammation.